Collapse Vulnerability of Reinforced Concrete Buildings Using Neural Networks - Alshaer, Imad Mohammad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
In this study, an Artificial Neural Network (ANN) analytical method has been developed for evaluation the collapse vulnerability (earthquake performance) of reinforced concrete (RC) buildings . In this study, collected total of 260 reinforced concrete buildings with 4 storey, that were chosen to represent the existing RC buildings. The commercial program Sta4CAD is used for modeling and analysing these buildings. The performance analysis of these 260 RC buildings have been used for training neural networks. The parameters that affect on earthquake performance represent the input and the performance represent the output. In this study 16 parameters have been thought to be effective on the performance of RC buildings were considered: Torsional Irregularity (A1), Slab Discontinuities (A2), Projections in Plan (A3), Weak Storey (B1), Soft Story (B2), Discontinuity of Vertical Structural Elements (B3), Weak Column – Strong Beam (C2), Stirrup Spacing (cm), Average Shear Wall Ratio, Average Column Ratio (CA) , Concrete Compression Strength (C), Type of Steel (Fy), Soil Type (Z), Turkish Earthquake Code (1975– 1997- 2007), Earthquake Zone (EZ) and Importance Factor (I). The output parameters are the Structural Performance (S1-S4) was obtained based on the 4 performance levels in Turkish Earthquake Code-2007 (TEC-2007). The performance analysis of RC buildings was performed according to both the linear performance analysis and nonlinear (static pushover analysis) procedures as specified in TEC-2007. iv The effect of each parameter tested in this study had various affecting ratios on the earthquake performance of the structure. It was found that shear wall ratio is the most significant structural components that affect. The projections in plan and slab discontinuities were determined to be the least significant parameters. According to the study, the prediction accuracy of ANN has been found 90% accuracy for nonlinear (pushover analysis method) and about 89% accuracy for linear performance analysis method. Keywords: Artificial neural network, collapse vulnerability, earthquake performance based design.

ÖZ: Bu çalışmada betonarme binaların deprem performanslarının değerlendirilmesi için yapay sinir ağları kullanılmıştır. Bu maksatla 4 katlı 260 betonarme bina seçilmiştir. Bu binalar Sta4CAD programı ile tasarlanmıştır. Binaların doğrusal elastik ve statik itme performans analiz sonuçları kullanılarak, yapay sinir ağı eğitilmiştir. Oluşturulan yapay sinir ağı sisteminde deprem performansını etkileyen parametreler girişi, yapı performans seviyesi ise çıkışı temsil etmektedir. Bu çalışmada deprem performansını etkileyeceği düşünülen 16 parametre seçilmiştir. Bunlar: Burulma Düzensizliği (A1), Döşeme Süreksizliği (A2), Planda Çıkıntılar Bulunması (A3), Zayıf Kat (B1), Yumuşak Kat (B2), Taşıyıcı Sistem Düşey Elemanlarının Süreksizliği (B3), Güçlü Kolon-Zayıf Kiriş (C2), Etriye Aralığı (cm), Ortalama Perde Duvar Oranı, Ortalama Kolon Oranı (CA), Beton Basınç Dayanımı (C), Çelik Türü (Fy), Zemin Türü (Z), Türk Deprem Yönetmeliği (1975 – 1997 – 2007), Deprem Bölgesi (EZ) ve Bina Önem Katsayısı (I)'dır. Çıkış parametreleri ise 2007 Türk Deprem Şartnamasi’nde (TEC-2007) bulunan 4 bina performans seviyesidir (S1-S4). Performans analizleri deprem şartnamesinde mevcut olan doğrusal elastik ve statik itme performans analiz yöntemlerine göre yapılmıştır. Bu çalışmada seçilen giriş parametreleri test edilmiş ve Ortalama Perde Duvar Oranının deprem performasında en önemli parametre olduğu saptanmıştır. Planda Çıkıntılar Bulunması ve Döşeme Süreksizliği parametreleri ise en az etkili parametreler olarak saptanmıştır. Bu çalışmanın sonucunda oluşturulan yapay sinir ağı sisteminde statik itme analizi yöntemi ile yapılan performans seviyesi tahminlerinin doğruluk oranının % 90, lineer performans analiz yöntemine göre yapılan performans seviyesi tahminlerinin doğruluk oranının ise % 89 olduğu saptanmıştır. Anahtar Kelimeler: Yapay sinir ağları, göçme riski, deprem performansına dayalı tasarım.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2016. Supervisor: Assist. Prof. Dr. Giray Özay.
Keywords: Civil Engineering; Earthquake resistant design; Earthquake resistant design-Concrete construction-Reinforced concrete; Buildings-Earthquake effects; Reinforced concrete-Reinforced concrete construction; Artificial neural network; collapse vulnerability; earthquake performance based design